Homicide, Acquisitive Crime, and Inflation: A City-Level Longitudinal Analysis - Rosenfeld, Richard (Crime & delinquency, 2023)
Building on research by Rosenfeld et al., citylevel random coefficients panel models reveal a significant association between inflation and homicide rates that is only partially mediated by acquisitive crime. Inflation is more strongly associated with homicide rates in more disadvantaged cities. The impact of inflation on public safety should be considered when setting and evaluating economic policy. Future research should address the mechanisms, in addition to acquisitive crime, that link homicide and inflation.